2022
DOI: 10.3390/jcm11041004
|View full text |Cite
|
Sign up to set email alerts
|

Abuse Potential of Cathinones in Humans: A Systematic Review

Abstract: Introduction and objective: Assessing the abuse potential of new substances with central nervous system activity is essential for preventing possible risks of misuse and addiction. The same methodology is recommended for the evaluation of the abuse potential of recreational drugs. This systematic review aims to assess the pharmacological effects related to the abuse potential and pharmacokinetics of cathinones, which are evaluated in both experimental and prospective observational studies in humans. Materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…Methylone exhibited an effect profile comparable to that of MDMA, with a faster onset and earlier disappearance of subjective effects than MDMA. Typically, the abuse potential of methylone follows the trend of other cathinones, such as natural cathinone and mephedrone (Poyatos et al, 2022b). MDMA exhibited effects similar to those previously reported in other published human studies (Camí et al, 2000;Kirkpatrick et al, 2014;Papaseit et al, 2016;Kuypers et al, 2017;Holze et al, 2020;Studerus et al, 2021).…”
Section: Discussionsupporting
confidence: 80%
“…Methylone exhibited an effect profile comparable to that of MDMA, with a faster onset and earlier disappearance of subjective effects than MDMA. Typically, the abuse potential of methylone follows the trend of other cathinones, such as natural cathinone and mephedrone (Poyatos et al, 2022b). MDMA exhibited effects similar to those previously reported in other published human studies (Camí et al, 2000;Kirkpatrick et al, 2014;Papaseit et al, 2016;Kuypers et al, 2017;Holze et al, 2020;Studerus et al, 2021).…”
Section: Discussionsupporting
confidence: 80%
“…In addition, when any drug induces desirable, euphoric and reinforcing effects, it may, to some extent, result in abuse and addictive potential. Regarding the sympathomimetics mentioned in this work, while cocaine addictive potential is recognized for several years [ 190 ], a new vision on cathinones has emerged with recent studies that recognize their abuse and addictive potential [ 177 , 222 ]. Actually, the addictive potential of some of these compounds adds another danger to the equation as chronic use will be likely and the set of toxic effects will increase.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that several drugs, including diethylpropion, lead to undesirable effects that can cause dependence and abuse. The authors point to the need for future research to prevent negative manifestations in the treatment of patients [ 59 ].…”
Section: Novel Drugs In Obesity Treatmentmentioning
confidence: 99%